Does accounting concervatism matter to mediate the relationship between gender diversity and financial performance: A Study on state-owned enterprises context - Rodiah, Siti; Samsiah, Siti; Muhammad, Nik Maheran Nik; Mairoza, Mairoza (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study seeks to examine more comprehensively how gender diversity on corporate boards influences the financial performance of Indonesian state-owned enterprises (SOEs), while also investigating whether accounting conservatism functions as a mediating variable in this relationship.Design/Methodology/Approach: The author used sample data of 27 SOEs listed on the Indonesia Stock Exchange during the 2019-2023 period, resulting in a total of 135 data observations. The authors used a regression model for hypothesis testing through STATA software and performed mediation testing with sobel tests.Research findings: Grounded in critical mass theory and agency theory, the empirical results reveal that gender diversity is not significantly associated with financial performance. However, accounting conservatism demonstrates a significant negative effect on financial performance. The mediating role of accounting conservatism in linking gender diversity to financial performance is not supported. Overall, these findings differ from several previous studies.Theoretical contribution/Originality: This research enriches the corporate governance literature by providing evidence on the effect of gender diversity on the financial performance of SOEs in Indonesia, a context that has not yet been widely explored. The key novelty of the study is the treatment of accounting conservatism as a mediating variable, whereas prior studies have primarily examined it as a direct determinant or moderator. Moreover, this study broadens the scope of Critical Mass Theory by linking conservative accounting behavior to the relationship between gender diversity and financial performance.Practitioner/Policy implication: The implications of this study provide valuable insights for SOE policymakers and managers in developing inclusive HR strategies and applying the principles of accounting conservatism to improve financial performance and transparency.Research limitation/Implication: The study is limited by the sample size and exclusion of other potential control variables. Future research should include more companies and external factors, such as regulations and macroeconomic conditions.